In vitro propagation of Eurycoma longifolia jack and comparison of genetic fidelity and antioxidant activity in in vivo plant - Alttaher, Annor Gebril Annour (2019)
Eurycoma longifolia Jack or Tongkat Ali as locally known in Malaysia is traditionally used as aphrodisiac and health supplement for various diseases. Due to its low rate germination, poor flowering, and its potential commercial value as a plantation crop as well as to conserve its germplasm, it is necessary to establish a suitable protocol of in vitro propagation as a better alternative for mass production of true-to-type plants. Hence, this study was conducted to develop an efficient protocol for Tongkat Ali micropropagation. Specific objectives were to induce in vitro adventitious shoot from the leaf and cotyledon explants and production of in vitro root biomass, to investigate the effect of different concentration of cytokinins on formation of multiple shoot from cotyledonary node explants, to assess the genetic fidelity of in vitro propagated plantlets, and to determine the total antioxidant content in in vitro and in vivo root extracts. Leaf and cotyledon explants were excised from in vitro seedlings for shoot regeneration; either indirectly through the callus or directly from the explant. The results showed the highest frequency of callus induction was 100% obtained from leaf explants on Murashige and Skoog (MS) medium supplemented with 1mg/L 2,4-dichlorophenoxy acetic acid (2,4-D) followed by 90% and 80% with 3.0 mg/L Dicamba and 1.0 mg/L Naphthaleneacetic acid (NAA) respectively. On the contrary, cotyledon explants produced the lowest percentage of callus at the all concentrations of auxins tested compared to leaf explants. Additionally, shoots were directly regenerated from leaf and cotyledon explants. The results revealed that 1.5 mg/L of 6-benzylaminopurine (BAP) gave an excellent response in shoot regeneration from both explants with an average of 1.8 ± 0.5 and 2.2 ± 0.4 shoots per explant respectively. On the other hand, root biomass was successfully produced from leaf explants in half-strength MS liquid medium containing various concentrations of indole-3-butyric acid (IBA) in combination with NAA. The result indicated that the highest fresh weight of root biomass was 9.18 ± 0.1g/L in a medium contained 0.5 mg/L IBA + 0.5 mg/L NAA within 6 weeks of culture. However, formation of multiple shoots was achieved by using cotyledonary node as an explant. The highest number (3.53 shoot per explant) obtained on MS medium supplemented with 1.0 mg/L BAP after 3 weeks. Besides, optimum rooting (3.20 roots per shoot) was achieved in half-strength MS medium containing 0.1 mg/L IBA. Platelets were successfully acclimatized to ex vitro conditions with 85% of survival percentage. Simple Sequence Repeat (SSR) and Inter Simple Sequence Repeat (ISSR) markers were tested to assess the genetic fidelity of the in vitro raised clones of E. longifolia. Out of the 12 SSR primers screened, nine primers produced 15 amplicons (1.7 bands in average) ranging from 100 to 800 bp, whereas eight ISSR primers generated 27 bands with an average of 3.4 bands ranging between 300 to 1000 bp. The monomorphic banding pattern confirmed the clonal homogeneity of the tissue culture-raised E. longifolia plantlets and reliability of the multiplication system used. Furthermore, different solvents were used for root extraction of in vitro and in vivo plants to determine the total antioxidant activity, total phenolic and flavonoid contents. Results of 1,1-diphenyl-2- picrylhydrazyl (DPPH) free radical scavenging method showed that in vitro root extract at 25°C exhibited maximum antioxidant activity with 0.114 mg TE/g DW. Meanwhile, Ferric Reducing Antioxidant Potential (FRAP) showed the highest antioxidant content with 0.075 mg TE/g DW in in vivo root extracts at 25ºC. On the other hand, in vivo root extracts with 0.09 mg GAE/g DW had maximum phenolic content at 4°C. Whereas, in vitro root extract at 25°C showed the highest total (0.31 mg GAE/g DW and 0.10 mg RE/g DW) of both polyphenol and flavonoid content respectively. From this study, the successful in vitro propagation of E. longifolia could provide a potential of large-scale production of planting materials in meeting the industrial and domestic demands.